PENGARUH MODEL PROJECT BASED LEARNING BERBASIS STEAM TERHADAP KETERAMPILAN BERPIKIR KREATIF SISWA KELAS V SEKOLAH DASAR - Amanda, Maysa; Grahito, Anggit; Jumanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Fifth-grade pupils across the KKG DAPIN II Diponegoro Cluster in Mojogedang Sub- district of Karanganyar Regency showed weak creative thinking. A field visit on 20 November 2025 found teachers leaning on lecturing and drill work. Teacher rating sheets marked roughly half the pupils as weak across fluency and flexibility as well as originality and elaboration. Such a gap prompted the trial reported here. What it set out to examine was the effect of STEAM-based Project Based Learning on the creative thinking of fifth-grade pupils in that cluster during the 2025/2026 school year. A quantitative route was chosen and a quasi-experiment ran under a nonequivalent control group design. Roughly 150 fifth-graders across six schools formed the population. Purposive sampling then narrowed the sample to 25 pupils of SD Negeri 3 Gentungan as the treated group alongside 25 pupils of SD Negeri 2 Gentungan as the untreated group. An essay test of five valid items carried the measurement and returned a Cronbach Alpha of 0.697. Descriptive statistics opened the analysis and a Shapiro-Wilk test together with a Levene test cleared the assumptions before an independent sample t-test settled the hypothesis. The treated group closed at a posttest mean of 86.00 while the untreated group reached only 71.20. A gap of 14.800 points emerged and significance fell to 0.000 which is below 0.05 so H0 could not stand. Cohen d reached 1.72 and lands in the very large band. STEAM-based PjBL therefore shapes creative thinking in a measurable way and deserves a place among IPAS learning options at primary level.